2019
DOI: 10.1002/hep.30651
|View full text |Cite
|
Sign up to set email alerts
|

A Bioreactor Technology for Modeling Fibrosis in Human and Rodent Precision‐Cut Liver Slices

Abstract: Precision cut liver slices (PCLSs) retain the structure and cellular composition of the native liver and represent an improved system to study liver fibrosis compared to two‐dimensional mono‐ or co‐cultures. The aim of this study was to develop a bioreactor system to increase the healthy life span of PCLSs and model fibrogenesis. PCLSs were generated from normal rat or human liver, or fibrotic rat liver, and cultured in our bioreactor. PCLS function was quantified by albumin enzyme‐linked immunosorbent assay (… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
81
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
5
2
1

Relationship

3
5

Authors

Journals

citations
Cited by 85 publications
(81 citation statements)
references
References 31 publications
0
81
0
Order By: Relevance
“…PCLS were generated as described in the Supporting Information. (29) PCLS were rested for 24 hours after the cutting; then, the first lipid treatment was applied. The free fatty acid (FFA) mix containing oleic, palmitic, linoleic, and elaidic acids (final concentration 2 mM, based on lipidomic studies performed on serum in NAFLD patients) was conjugated to fatty acid-depleted bovine serum albumin (final concentration 0.2 mM; Sigma).…”
Section: Lipid Treatmentsmentioning
confidence: 99%
“…PCLS were generated as described in the Supporting Information. (29) PCLS were rested for 24 hours after the cutting; then, the first lipid treatment was applied. The free fatty acid (FFA) mix containing oleic, palmitic, linoleic, and elaidic acids (final concentration 2 mM, based on lipidomic studies performed on serum in NAFLD patients) was conjugated to fatty acid-depleted bovine serum albumin (final concentration 0.2 mM; Sigma).…”
Section: Lipid Treatmentsmentioning
confidence: 99%
“…This model is also not specific to cryptococcal infection so can be used with any pulmonary pathogen, providing a great opportunity to study polymicrobial infections. Finally, this technique is also not limited to the lung, and has also been adapted for use with other organs, such as the liver (40).…”
Section: Discussionmentioning
confidence: 99%
“…hPCLS also reflect the liver cell heterogeneity and better preserve liver histoarchitecture, allowing for the interplay between parenchymal and nonparenchymal liver cells (NPCs) as well as liver infiltrating immune cells (Palma et al 2019). It is reported that, when cultured under proper conditions, hPCLS can preserve their viability for up to 5 days (Paish et al 2019;Wu et al 2018), which enhances their utilization for studying the pathophysiological processes in a variety of hepatic diseases, such as alcoholic liver disease, non-alcoholic fatty liver disease (NAFLD), fibrosis and cirrhosis, cholestasis and DILI (Palma et al 2019). Nowadays, human liver slice-derived cultures combined with omics techniques have been used to study the mechanisms of drug-induced hepatotoxicity (Elferink et al 2011), steatosis (Ijssennagger et al 2016) and cholestasis (Vatakuti et al 2017).…”
Section: Precision-cut Liver Slicesmentioning
confidence: 99%
“…Further to this, PCLS maintained in a static culture medium usually display a limited lifespan of 24-48 h (Jiang et al 2015b). Advanced culture systems such as microfluidic perfusion systems (Khong et al 2007), bioreactor systems (Paish et al 2019) and air-liquid interface culture systems (Wu et al 2018) have been shown to improve their longevity for 3-15 days, while the cultured PCLS still cannot preserve high levels of hepatic function for over 3 days without evident fibrogenesis and necrosis/apoptosis in the model (Lin and Khetani 2016;Paish et al 2019).…”
Section: Precision-cut Liver Slicesmentioning
confidence: 99%